Polygamy in the History of Early Islamic Civilization: A Study of Islamic Law, Social Context, and the Practices of the Prophet - Ahmad Muzakki; Akhmad Zaeni; Vita Firdausiyah; Abdullah Rosikh Fil Ilmi (TSAQAFAH, 2025)
Polygamy is a crucial topic in both classical and contemporary Islamic studies, especially in the context of gender justice and family law. This study aims to examine polygamy in the history of early Islamic civilisation through three main aspects: (1) normative analysis of the verses of the Qur'an that regulate polygamy, particularly QS. An-Nisa' verses 3 and 129; (2) the socio-cultural contextualisation of pre-Islamic and prophetic Arab society that underlies these regulations; and (3) an examination of the Prophet Muhammad's practice of polygamy as an applicable model of Sharia law. The issues examined include: the normative message of the verses on polygamy; how the social context influences Sharia policy; and how the Prophet's practice affirms moral and social principles in polygamy. This study uses a qualitative method based on library research with a maqāṣidī interpretation approach, contextual hermeneutics, and historical analysis of texts and practices. The results show that polygamy in early Islam was a form of regulation of pre-Islamic practices, with very strict limitations based on multidimensional justice. The practices of the Prophet Muhammad SAW prove that polygamy was not a general recommendation, but rather a solution in certain social conditions, particularly for the protection of women and social reconciliation. In conclusion, polygamy in early Islam was a dispensation (rukhṣah) that could only be justified if certain moral, social, and spiritual conditions were met, not as an ideal norm. These findings emphasise the importance of a contextual approach in re-reading normative texts to respond to current socio-cultural challenges.